Market Domination Through Social Media and E-commerce Merger in Business Competition Law’s Perspective - Esmeralda Ivana Rismauli; Suherman, Suherman (Dinasti Research, 2024)
The merger of social media and e-commerce has a significant impact on market competition. This study, “Market Domination Through Social Media and E-commerce in Business Competition Law’s Perspective”, analyzes the legal aspects related to the merger of two platforms, focuses on the legal implications for business competition. This research uses a normative legal approach to identify and analyze relevant legal regulations related to business competition and to evaluate whether the merger violates applicable legal principles. The results of this study are expected to provide a better understanding of the role of law in regulating the dynamics of the rapidly developing digital market, especially in the face of the phenomenon of mergers between social media and e-commerce. The legal implications of the merger between social media and e-commerce will be discussed, and the comparison of Indonesian and Singaporean Competition Law that creates recommendations for more effective legal policies to ensure protection against fair business competition and consumer interests. This study has highlighted the urgent need for Indonesia to modernize its competition law framework to effectively address the challenges and opportunities and to tackle the complexities and nuances of the digital landscape.